PELAKSANAAN UNDANG-UNDANG NOMOR 18 TAHUN 2013 TENTANG PENCEGAHAN DAN PEMBERANTASAN PERUSAKAN HUTAN DI KECAMATAN PANGEAN KABUPATEN KUANTAN SINGINGI - Syahrizal, Syahrizal (Wahana Forestra: Jurnal Kehutanan, 2016)
Environmental damage caused by illegal logging is already being felt by some people, so that led to misunderstandings and disputes between citizens. The study was conducted in the District Pangean Singingi Kuantan District. Some problems that occurred in district of Pangean; how the implementation of Law No. 18 2013 and role of the Government and obstacles in the prevention and forest destruction in the district of Pangean Regency Kuantan Sengingi. The research objective is; to explain the implementation of Law No. 18 2013 in the district of Pangean. Related to the Government's role in the prevention and forest destruction and barriers in the prevention of forest destruction in the district of Pangean Regency Kuantan Singingi. The results of this study are that; Implementation of Law Number 18 2013 has been socialized to the community leaders and companies in Kuantan Singingi; role of government in the implementation of the prevention of forest destruction has been carried through in the form of patrol surveillance, raids and joint operations ; Obstacles in the prevention of forest destruction is that the pressure from local police officers or government officials, so that the perpetrators of forest encroachment continues to run because they feel protected.